The Analysis of Online Worship Services Acceptance using the UTAUT 2 Method and Clustering k-Means - Gilang Jonathan Phita; Yessica Nataliani (Sistemasi: Jurnal Sistem Informasi, 2022)
The characteristics and background of the church congregation and the acceptance of technology in online worship services were one of the parameter to determine user attitudes or behavior in accepting technology. The objective of this research to is to find out the acceptance of church congregation's technology toward the online worship services using the Unified Theory of Acceptance and Use of The Technology 2 (UTAUT 2), and answers of respondents from various backgrounds and ages were grouped using k-Means clustering. Data were collected through a questionnaire with a total of 220 respondents. From the UTAUT 2 method using multiple linear regression, it was found that the Habit variable on the use of online worship has a high influence toward the Behavioral Intention variable, and the Habit variable on the use of online worship has a high influence toward the Use Behavior variable. Furthermore, clustering with k-Means was carried out to see the age group that was satisfied with online worship services, based on four clusters obtained using the Elbow method and six age groups. The results of the k-Means clustering of all UTAUT 2 variables, the age group 12-16 years and 26-35 years are the most satisfied group and accept online worship services.